Behavioral intervention research in hospice and palliative care : building an evidence base - Demiris, George; Parker-Oliver, Debra, 1960-; Washington, Karla T. (Elsevier : Academic Press, 2019)
"Behavioral Intervention Research in Hospice and Palliative Care: Building an Evidence Base sets forth research considerations and guidelines to build evidence-based interventions to improve end-of-life care. It is an in-depth introduction to implementation research and showcases how a clinical need is identified to inform an intervention. The book extensively examines the various phases of intervention research, including design, implementation, evaluation, dissemination and translation. The book focuses on methodological, ethical and practical issues. The science behind the quality of hospice and palliative care lags behind that of traditional medical practice, despite the continuous growth of palliative care interdisciplinary teams. Researching, developing and testing strategies is essential to advancing the effectiveness and value of this care. Informs readers how to conduct intervention research toward identifying best care Advises readers on design, implementation and evaluation of research Provides step-by-step templates to develop an intervention study Includes mock protocols from successful intervention trials Synthesizes lessons learned by established intervention researchers in hospice and palliative care."--Publisher description